Salpingectomy for ectopic pregnancy: Does length really matter? - Gaughran, Jonathan; Mitchell, Sian; Holland, Tom (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
This abstract describes a case of a tubal stump ectopic. The aetiology, presentation and management of such rare cases are described. The evidence bases for the rationale for leaving a short versus a long stump at salpingectomy is reviewed.